Firm-Specific Biases in the Capital Markets' Response : an Empirical Evidence for the NYSE and the LSE - Czapiewski, Leszek; Lizińska, Joanna (Zniekształcenia pomiaru reakcji rynku kapitałowego - studium empiryczne dla nowojorskiej i londyńskiej giełdy papierów wartościowych, 2010)
Firms announcing splits or acquiring other companies usually have some common characteristics that can be expressed by a market or book value or are explained by financial ratios. We conduct an event study over the trading period between 1985 and 2008 for the New York Stock Exchange and the London Stock Exchange. For randomly selected event dates, securities are randomly chosen from sub-samples of firms that have similar characteristics. Mean abnormal returns that are significantly different from zero are observed for some characteristic-based subsamples. As significant mean forecast biases exist, it is suggested that results of event studies for samples when firms share some common characteristics should be concluded very cautiously.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s.17-27
Keywords: event study; capital market